Effects of alpha-mangostin on the expression of anti-inflammatory genes in U937 cells - Liu Szu-Hsiu; Lee Lain-Tze; Hu Nai-Yun; Huange Kuo-Kuei; Shih Ying-Chu; Munekazu Iinuma; Li Jen-Ming; Chou Ting-Yu; Wang Wei-Hsin; Chen Ting-Shou (BMC, 2012)
Abstract Background α-Mangostin (α-MG) is a main constituent of the fruit hull of the mangosteen. Previous studies have shown that α-MG has pharmacological activities such as antioxidant, antitumor, anti-inflammatory, antiallergic, antibacterial, antifungal and antiviral effects. This study aims to investigate the anti-inflammatory molecular action of α-MG on gene expression profiles. Methods U937 and EL4 cells were treated with different concentrations of α-MG in the presence of 0.1 ng/mL lipopolysaccharide (LPS) for 4 h. The anti-inflammatory effects of α-MG were measured by the levels of tumor necrosis factor (TNF)-α and interleukin (IL)-4 in cell culture media, which were determined with enzyme-linked immunosorbent assay kits. The gene expression profiles of all samples were analyzed with a whole human genome microarray, Illumina BeadChip WG-6 version 3, containing 48804 probes. The protein levels were determined by Western blotting analyses. Results α-MG decreased the LPS induction of the inflammatory cytokines TNF-α (P = 0.038) and IL-4 (P = 0.04). α-MG decreased the gene expressions in oncostatin M signaling via mitogen-activated protein kinase (MAPK) pathways, including extracellular signal-regulated kinases (P = 0.016), c-Jun N-terminal kinase (P = 0.01) , and p38 (P = 0.008). α-MG treatment of U937 cells reduced the phosphorylation of MAPK kinase 3 / MAPK kinase 6 (P = 0.0441), MAPK-activated protein kinase-2 (P = 0.0453), signal transducers and activators of transcription-1 (STAT1) (P = 0.0012), c-Fos (P = 0.04), c-Jun (P = 0.019) and Ets-like molecule 1 (Elk-1) (P = 0.038). Conclusion This study demonstrates that α-MG attenuates LPS-mediated activation of MAPK, STAT1, c-Fos, c-Jun and EIK-1, inhibiting TNF-α and IL-4 production in U937 cells.